2020
DOI: 10.1523/jneurosci.2809-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Amino Acids Impact LRRK2-Induced Neurodegeneration in Parkinson's Disease Models

Abstract: The G2019S mutation in leucine-rich repeat kinase 2 (LRRK2) is a common cause of Parkinson's disease (PD) and results in age-related dopamine neuron loss and locomotor dysfunction in Drosophila melanogaster through an aberrant increase in bulk neuronal protein synthesis. Under non-pathologic conditions, protein synthesis is tightly controlled by metabolic regulation. Whether nutritional and metabolic influences on protein synthesis can modulate the pathogenic effect of LRRK2 on protein synthesis and thereby im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Amino groups, primarily responsible for amino acid synthesis in organisms, are formed by glutamic acid and glutamine in the body. The increased amino acid content in the intestinal tract may inhibit neurological degeneration via stress response, such as alleviating Parkinson's phenotypes [40]. An experiment involving the effect of nicotine on the gutbrain axis in mice revealed that it caused changes in the gut microbiota and glutamate metabolism that affected the mice's gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…Amino groups, primarily responsible for amino acid synthesis in organisms, are formed by glutamic acid and glutamine in the body. The increased amino acid content in the intestinal tract may inhibit neurological degeneration via stress response, such as alleviating Parkinson's phenotypes [40]. An experiment involving the effect of nicotine on the gutbrain axis in mice revealed that it caused changes in the gut microbiota and glutamate metabolism that affected the mice's gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether TOR inhibition plays a role in the protective impact of AMPK activation, since autophagy can be induced via AMPK signaling which is a feasible mechanism. Work from our own laboratory indicates that LRRK2 G2019S expressing flies chronically fed a moderately elevated amino acid diet across adulthood are protected from age-related loss of dopamine neurons and locomotor dysfunction observed in these flies on a standard diet in a mechanism that involves induction of AMPK activity by the fly Sestrin ortholog and consequent upregulation of autophagy [ 165 ]. TOR inhibition may be neuroprotective in the context of LRRK2 G2019S, since enhanced vulnerability to valinomycin-induced cytotoxicity seen in LRRK2 G2019S iPSC-derived neural cells from familial PD patients can be attenuated by treating them with rapamycin [ 166 ] consistent with TOR involvement.…”
Section: Metabolism At the Intersection Of Aging And Pdmentioning
confidence: 99%
“…These stressors activate AMPK, which then phosphorylates α-synuclein, causing it to aggregate and eventually cause neurodegeneration [75]. In addition, reduced protein synthesis induced by AMPK activation could also cause neurodegeneration [111]. However, AMPK may also exert a neuroprotective effect by stimulating the destruction of damaged mitochondria and α-synuclein aggregates through autophagy [112,113].…”
Section: Ampk Signaling In Nddsmentioning
confidence: 99%